2015
DOI: 10.1021/acs.energyfuels.5b00948
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Gas-Phase As2O3 by Metal Oxide Adsorbents: Effects of Experimental Conditions and Evaluation of Adsorption Mechanism

Abstract: This research studies the adsorption of gas-phase As 2 O 3 by CaO, Fe 2 O 3 and Al 2 O 3 , using a fixed-bed reactor with an arsenic continuous generation device. The adsorption of gas-phase arsenic on CaO and Fe 2 O 3 is mainly chemical adsorption at 600−900 °C. The adsorption quantity and efficiency decreases as the temperature increases. Iron(III) oxide has the best arsenic adsorption ability, followed by calcium oxide and then aluminum oxide. The incoming arsenic concentration was varied, from 4.5 × 10 −6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…Kinetic parameters could be signficantly different because different kinetic equations were adopted and different experimental parameters were applied. However, the reaction order with respect to arsenic concentration is close to 1, which appears to be a common conclusion [69,71,75,80,237].…”
Section: Kinetic Studiesmentioning
confidence: 67%
See 3 more Smart Citations
“…Kinetic parameters could be signficantly different because different kinetic equations were adopted and different experimental parameters were applied. However, the reaction order with respect to arsenic concentration is close to 1, which appears to be a common conclusion [69,71,75,80,237].…”
Section: Kinetic Studiesmentioning
confidence: 67%
“…In the recent work of Zhang et al [75], the conclusions of Chen et al [81] were partially validated. Furthermore, through thermodynamic simulation, Zhang et al [75] found that the adsorption process (described as Eq.2) was an exothermic reaction which could explain the temperature impact on arsenic.…”
Section: Effect Of Temperaturementioning
confidence: 94%
See 2 more Smart Citations
“…Shen et al (2015) maintained that CaO could react with arsenic compounds to form Ca (AsO 2 ) 2 above 1273 K by calculation. Zhang et al (2015) believed that As 2 O 3 steam could be absorbed by ferric oxide (Fe 2 O 3 ) and transformed to iron arsenate (FeAsO 4 ). However, most of these experiments were only conducted to investigate the interactions between As 2 O 3 and CaO/Fe 2 O 3 , and some of above interactions were put forward in oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%